Demographic, natural and anthropogenic drivers for coastal Cultural ecosystem services in the Falkland Islands. (November 2021) - Blake, Denise; Carver, Stephen; Ziv, Guy
Highlights: Our study provides a case study to analyse the location of CES in small islands. Our analysis provides an insight for managers and conservationists. Groups of people locate their CES in different places. A range of different socio-demographic and environmental factors drives this. Abstract: People of remote oceanic islands show a clear connection to their natural environment. Our study provides a case study example of how the location of coastal Cultural Ecosystem Services in small islands can be analysed, providing useful information to managers and conservationists alike. Using a series of analyses, we here show how groups of people place Cultural Ecosystem Services in different places driven by their socio-demographic identity and the environment that surrounds them. We found that a range of different socio-demographic factors affects the grouping of people and that both natural and anthropogenic infrastructure environments affect the location of recreational and aesthetic services. For recreation and aesthetic services, we found that a range of environmental features, including the travel distance and accessibility, habitat types, biodiversity indicators and proximity to Invasive Species impacted the location of these coastal services. As a result, our demographic identity can identify places where services are located.